2018
DOI: 10.3390/coatings8040122
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Sprayed AZ91D Coating and SiC/AZ91D Composite Coatings

Abstract: As an emerging coating building technique, cold spraying has many advantages to elaborate Mg alloy workpieces. In this study, AZ91D coatings and AZ91D-based composite coatings were deposited using cold spraying. Coatings were prepared using different gas temperatures to obtain the available main gas temperature. Compressed air was used as the accelerating gas, and although magnesium alloy is oxidation-sensitive, AZ91D coatings with good performance were obtained. The results show that dense coatings can be fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The difference may result from the different size of specimens and different resolution of techniques. The non-connected porosity of low level and small size promises good corrosion protection for the aluminum substrate [33,34]. In Figure 5, the porosity fraction along the certain axis is the porosity measured on the series of planes that are vertical to the assigned axis based on the grey level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference may result from the different size of specimens and different resolution of techniques. The non-connected porosity of low level and small size promises good corrosion protection for the aluminum substrate [33,34]. In Figure 5, the porosity fraction along the certain axis is the porosity measured on the series of planes that are vertical to the assigned axis based on the grey level.…”
Section: Resultsmentioning
confidence: 99%
“…The difference may result from the different size of specimens and different resolution of techniques. The non-connected porosity of low level and small size promises good corrosion protection for the aluminum substrate [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Bilal et al [17] and our group [18] have confirmed the excellent structure and corrosion resistance of poly(o-toluidine). As a very stable inorganic material, silicon carbide (SiC) has been widely used in the reinforcement phase of composite materials or coatings [19]. Based on that, in order to study the effect of methyl substituent on the structure and corrosion resistance of PANI, we synthesized poly(o/m-toluidine) and applied it to the surface of composite SiC/Zn coating.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, it can be seen that the FWHM gradually Figure 8 depicts the XRD patterns of the as-sprayed coatings on Al6061 alloy substrate. Visually, there appears to be no evidence of either a phase transformation or oxidation with the coatings, which is typically seen from the CS process due to the hammering effects of the particles [88] and also low temperature deposition nature of the CS process [89]. For all specimens, the crystalline planes and phase structures also seem to be the same, primarily having a hexagonal close packed (α) crystal system.…”
Section: Microstructure Of the Coatingsmentioning
confidence: 92%